A balloon‐assisted endoscopic submucosal dissection using long colonoscope and guidewire - Yu Watahiki; Kazumasa Kawashima; Takuto Hikichi; Tadayuki Takagi; Michio Onizawa; Naohiko Gunji; Chiharu Watanabe; Jun Wada; Yuka Oka; Yuko Hashimoto; Hiromasa Ohira (DEN Open)
Abstract Balloon‐assisted endoscopy enables stable endoscopic maneuverability. Balloon‐assisted endoscopic submucosal dissection (BA‐ESD) is useful in the treatment of proximal colorectal tumors where scope maneuverability is poor. Herein, we reported a case in which BA‐ESD was successfully performed using a long colonoscope with a guidewire, although the lesion could not be reached using the balloon‐assisted endoscopy technique with a therapeutic colonoscopy. A 50‐year‐old man underwent a colonoscopy that revealed a tumor in the ascending colon. BA‐ESD was performed using a conventional therapeutic endoscope due to excessive intestinal elongation and poor endoscopic maneuverability. However, the transverse colon loop could not be reduced, and the total colonoscopy failed despite using balloon‐assisted endoscopy. The scope was then changed from a conventional colonoscope to a long colonoscope, inserted into the terminal ileum, and the loop was reduced. After the guidewire was placed at the terminal ileum and the long colonoscope was removed, a therapeutic colonoscopy with an overtube was inserted into the ascending colon without reforming the colonic loop, allowing safe BA‐ESD.